Superbusiness : how I started SuperJam from my gran's kitchen - Doherty, Fraser (Capstone, 2011)
'Fraser gives hope to anyone who ever dreamed of selling to a wider market' Lorraine Kelly 'You have a great story to tell' Gordon Brown 'Fraser is an exciting young entrepreneur with an amazing story. His jams taste really fantastic too!' Duncan Bannatyne At just 14 years old, Fraser Doherty was selling jars of homemade jam to his neighbours. A few years later, SuperJam was flying off the shelves of the world's largest supermarket chains. SuperBusiness tells how he transformed a hobby into a much-loved brand, selling millions of jars along the way. Fraser explains how he did it - from his own kitchen table, without huge investment - and how you too, can come up with a killer idea, build a brand, make money, and do good in your community. Those crazy business ideas really can grow into something amazing and life changing. If this story doesn't inspire you to start your adventure, nothing will.